Decisive role of ozone formation control in winter PM2.5 mitigation in Shenzhen, China. (15th May 2022) - Tang, Meng-Xue; Huang, Xiao-Feng; Sun, Tian-Le; Cheng, Yong; Luo, Yao; Chen, Zheng; Lin, Xiao-Yu; Cao, Li-Ming; Zhai, Yu-Hong; He, Ling-Yan
Abstract: During the COVID-19 lockdown, atmospheric PM2.5 in the Pearl River Delta (PRD) showed the highest reduction in China, but the reasons, being a critical question for future air quality policy design, are not yet clear. In this study, we analyzed the relationships among gaseous precursors, secondary aerosols and atmospheric oxidation capacity in Shenzhen, a megacity in the PRD, during the lockdown period in 2020 and the same period in 2021. The comprehensive observational datasets showed large lockdown declines in all primary and secondary pollutants (including O3 ). We found that, however, the daytime concentrations of secondary aerosols during the lockdown period and normal period were rather similar when the corresponding odd oxygen (O x ≡O3 +NO2, an indicator of photochemical processing avoiding the titration effect of O3 by freshly emitted NO) were at similar levels. Therefore, reduced O x, rather than the large reduction in precursors, was a direct driver to achieve the decline in secondary aerosols. Moreover, O x was also found to determine the spatial distribution of intercity PM2.5 levels in winter PRD. Thus, an effective strategy for winter PM2.5 mitigation should emphasize on control of winter O3 formation in the PRD and other regions with similar conditions. Graphical abstract: Image 1 Highlights: All primary and secondary air pollutants showed a lockdown decline in Shenzhen. Reduced O x rather than precursors was a direct driver to reduce secondary aerosols. O x also determined the spatial distribution of intercity PM2.5 levels in winter. Effective strategy for winter PM2.5 mitigation need control winter O3 formation.